A proposed framework based on literature review of online contextual mental health services to enhance wellbeing and address psychopathology during COVID-19 - Tanhan, Ahmet; Yavuz, K.F.; Young, J. S.; Nalbant, A.; Arslan, G.; Yıldırım, M.; Ulusoy, S.; Genç, Emel; Uğur, E.; Çiçek, İ.; Genç, Emel (Electronic Journal of General Medicine, 2020)
Coronavirus disease (COVID-19) became a pandemic and is causing unprecedented biopsychosocial, spiritual and economic issues across the world while mostly affecting unprivileged populations. Turkey has gradually implemented new regulations, which slowly affected the entire country and increased the need for mental health services disproportionally. We conducted a comprehensive literature review on mental health in Turkey during COVID-19. There was no well-grounded peer-reviewed manuscripts or projects utilized a framework. Therefore, we wrote this manuscript to provide a conceptual framework grounded in ecological systems theory, acceptance and commitment therapy, and community-based participatory action research to introduce contextually evidence-based online mental health services: hotline, psychiatric interview, counseling, and Read-Reflect-Share group bibliotherapy. The framework aims to (1) address biopsychosocial spiritual and economic issues, (2) enhance wellbeing, and (3) empower the mental health profession in research and practice. Our preliminary findings and clinical experience indicated that the proposed framework and interventions derived from the framework enhanced wellbeing and decreased psychopathological symptoms in experimental group compared to control groups. Based on the preliminary analysis, most of the online, phone based, or face-to-face mental health services introduced in this manuscript were highly recommended by the participants to be provided to general public during and after COVID-19. Mental health professionals and authorities can use the proposed framework and interventions to develop interventions and research in order to alleviate pandemic-based biopsychosocial spiritual and economic issues and enhance wellbeing.
Keywords: COVID-19; Online mental health; Acceptance and commitment therapy; Psychopathology; Positive psychology; Ecological system theory; Pandemic; Telemental health; Çevrimiçi ruh sağlığı; Kabul ve bağlılık terapisi; Psikopatoloji; Pozitif psikoloji; Ekolojik sistem teorisi; Pandemi; Telemental sağlık